The Tax - Handous, Abdelhakim (Journal of Asian Business Strategy, 2013)
The traditional fiscal policy of the nation is multidimensional. The traditional tax rates are variable and the basis for calculating the tax on corporate profits is biased. The purpose of this article is to show that the optimal allocation of resources in the economy tax rate is constant and is equal to 20% and the basis for calculating the tax on corporate profits is the accounting profit before amortization decreased by the regulatory amortization of immobilizations, the dividend income, reversals of provisions and deferred losses and increased by endowments to provisions and that of the tax on personal income is their gross salary. It tells the truth that it is not tax other than the tax on corporate profits, the tax on personal income and the registration fee.